Biological Evaluation and Theoretical Study of Bi-dentate Ligand for Amoxicillin Derivative with Some Metal Ions (Baghdad Science Journal, 2021)
In this paper, the complexes of Shiff base of Methyl -6-[2-(diphenylmethylene)amino)-2-(4-hydroxyphenyl)acetamido]-2,2-dimethyl-5-oxo-1-thia-4-azabicyclo[3.2.0]heptane-3-carboxylate (L) with Cobalt(II), Nickel(II), Cupper(II) and Zinc(II) have been prepared. The compounds have been characterized by different means such as FT-IR, UV-Vis, magnetic moment, elemental microanalyses (C.H.N), atomic absorption, and molar conductance. It is obvious when looking at the spectral study that the overall complexes obtained as monomeric structure as well as the metals center moieties are two-coordinated with octahedral geometry excepting Co complexes that existed as a tetrahedral geometry. Hyper Chem-8.0.7 program was employed, after calculating the heat of formation (ΔH°f), binding energy (ΔEb), dipole moment( µ ), and FT-IR frequencies are carried out in gas phase, the geometric shape is suggested. The compounds have been also screened for their bioactivity to antibacterial and antifungal.